Engaging alumni entrepreneurs in the student entrepreneurship development process: A social network perspective. Issue 5 (28th July 2020) - Tang, Mingfeng; Yang, Chen; Baskaran, Angathevar; Tan, Jianwei
Abstract : Using the social network perspective and a case study of Chongqing Jiaotong University, this study analyzes the engagement of alumni entrepreneurs in the university student entrepreneurship development process in China. It employs primary data gathered through interviews of senior university managers, alumni and student entrepreneurs, and student start-ups. The study found that the importance of alumni entrepreneurs is comparatively weak at the formation stage of student entrepreneurial intention but relatively strong at the entrepreneurial resource acquisition stage. The most important resource provided by the alumni is information, followed by materials, clients, and human, technological and financial resources. Professors play the most important role in nurturing student entrepreneurship, both at the formation stage and the resource acquisition stage. The findings suggest that universities should involve alumni entrepreneurs actively to foster student entrepreneurship as well as incentivize professors to proactively nurture student entrepreneurs.